MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PENJUMLAHAN PECAHAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA SISWA KELAS V SDN MANTUIL 1 BANJARMASIN - Amalia Rizkina (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2019)
This research aims to find out teacher’s activity, students’ activity, and students’ learning result in 5th grade in the lesson of fractional addition with cooperative learning model type of Problem Based Learning. The type of this research is classroom action research. The setting of this research is 5th grade students in SDN Mantuil 1 Banjarmasin in the academic year 2019/2020 whit 24 students, consisted of 11 male students and 13 female students. The data source is obtained from the teacher, students, and students’ learning results. The data is analyzed with the condition teacher’s activity is considered successful if there are 81% (very active) of students get the score of 66 at the minimum and classically if there are 81% of students get the score of ≥ 66.